SPEAKING DIFFICULTIES FACED BY HOTELIER STUDENTS OF STIPARY IN THE ACADEMIC YEAR 2019/2020 - Tyas Purnawati (JELLT (Journal of English Language and Language Teaching), 2021)
This paper discusses the difficulties faced by hotelier students of STIPARY. From both observation and interview, this study reveals that all students encountered various difficulties in English speaking ability. The prevalent problem faced by the students was ‘lack of vocabulary’, while ‘being afraid of making mistakes’ was the prime cause of problem which hindered them to speak. The students had striven to cope with their problems in learning speaking, but their attempts had not been yet ample and successful.